2019
DOI: 10.1371/journal.pone.0218437
|View full text |Cite
|
Sign up to set email alerts
|

Preeclampsia and intrauterine growth restriction: Role of human umbilical cord mesenchymal stem cells-trophoblast cross-talk

Abstract: Background Oxidative stress is involved in the pathogenesis and maintenance of pregnancy-related disorders, such as intrauterine growth restriction (IUGR) and preeclampsia (PE). Human umbilical cord mesenchymal stem cells (hUMSCs) have been suggested as a possible therapeutic tool for the treatment of pregnancy-related disorders in view of their paracrine actions on trophoblast cells. Objectives To quantify the plasma markers of peroxidation in patients affected by PE a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 71 publications
1
39
1
1
Order By: Relevance
“…Preeclampsia has been widely considered as an independent risk factor that largely contributes to IUGR [41]. In the current research, the prevalence of IUGR (19 %) was slightly lower than the rates previously reported by some studies [42] and higher than others [43].…”
Section: Discussioncontrasting
confidence: 69%
“…Preeclampsia has been widely considered as an independent risk factor that largely contributes to IUGR [41]. In the current research, the prevalence of IUGR (19 %) was slightly lower than the rates previously reported by some studies [42] and higher than others [43].…”
Section: Discussioncontrasting
confidence: 69%
“…TBARS were determined as MDA release. The MDA measurement was performed by using the TBARS assay Kit (Cayman Chemical), as previously [36,38]. For the assays, 100 µL of each plasma sample was added to 100 µL of sodium dodecyl sulfate (SDS) solution and 2 mL of the Color Reagent, following the manufacturer's instructions.…”
Section: Tbars Quantificationmentioning
confidence: 99%
“…Cell viability was examined in Huh7.5 cells and primary human hepatocytes by using the 1% 3-[4,5-dimethylthiazol-2yl]-2,5-diphenyl tetrazolium bromide (MTT; Life Technologies Italia, Monza, Italy; catalog number CT02) dye, as previously performed (17)(18)(19)(20)(21) and described in Supplementary Material. Cell viability was determined by measuring the absorbance through a spectrometer (VICTOR TM X Multilabel Plate Reader; PerkinElmer) with a wavelength of 570 nm and cell viability was calculated by setting control cells as 100%.…”
Section: ) Cell Viabilitymentioning
confidence: 99%
“…At the end of stimulation, Huh7.5 cells were lysed in iced Ripa buffer supplemented with sodium orthovanadate (2 mM; Sigma) and protease inhibitors cocktail (1 mM; Thermo Fisher Scientific) and phenylmethanesulfonyl fluoride (1 mM; Sigma). The extracted proteins were quantified through bicinchoninic acid protein (BCA, Pierce) and used for electrophoresis and immunoblotting studies (16)(17)(18)(19)(20)(21)(22). Due to shortage of plasma specimens, experiments were conducted with plasma taken from three NAFLD patients and three healthy subjects and were repeated at least three times.…”
Section: ) Cell Lysatesmentioning
confidence: 99%